2017
DOI: 10.1088/1361-6528/aa6615
|View full text |Cite
|
Sign up to set email alerts
|

New insights on laser-induced graphene electrodes for flexible supercapacitors: tunable morphology and physical properties

Abstract: In certain polymers the graphenization of carbon atoms can be obtained by laser writing owing to the easy absorption of long-wavelength radiation, which generates photo-thermal effects. On a polyimide surface this process allows the formation of a nanostructured and porous carbon network known as laser-induced graphene (LIG). Herein we report on the effect of the process parameters on the morphology and physical properties of LIG nanostructures. We show that the scan speed and the frequency of the incident rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 38 publications
5
82
0
1
Order By: Relevance
“…A total of 10 pairs of electrode fingers were fabricated for the interdigital supercapacitors by programmed laser scanning pattern, with each finger having an active length of 10 mm and a width of 0.5 mm. From the low magnification image (Figure 2a), a continuous and porous membrane made up of many irregular particles was presented on the surface of the laser irradiated polyimide sheets, in contrast to the reported shapes of flakes [4] needles [11] and fiber. Detailed electrodes design information is also provided in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…A total of 10 pairs of electrode fingers were fabricated for the interdigital supercapacitors by programmed laser scanning pattern, with each finger having an active length of 10 mm and a width of 0.5 mm. From the low magnification image (Figure 2a), a continuous and porous membrane made up of many irregular particles was presented on the surface of the laser irradiated polyimide sheets, in contrast to the reported shapes of flakes [4] needles [11] and fiber. Detailed electrodes design information is also provided in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
“…[20] The slightly higher value (0.899) indicates the generation of large amounts of defects or heteroatom doping within these carbon polyhedra. [11] The wettability of the laser irradiated polyimide surface with the electrolyte is a crucial factor for practical application and the hydrophilicity of film is particularly desired for the water-based electrolytes. [21] Toward the application as electrode materials for supercapacitors, it is pivotal to uncover the chemical environments of the heteroatoms in the carbon matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Aer the release of these molecules, the aromatic compounds can be rearranged to form few-layer graphene nanostructures. 31,32 This pyrolysis/carbonisation proceeds at a very fast rate due to the rapid laser heating inherent to the laser-writing process. 35 Additionally, it was also observed that with the increase of the scan speed (>350 mm s À1 ) the uniformity of the samples was reduced, showing alternating regions of high and low porosity, likely to be due to the non-uniform exposition of the precursors to the laser.…”
Section: Microscopical Analysesmentioning
confidence: 99%
“…34 Following the work of Lin et al, 31 several others have been reported regarding the development, optimisation and application of LIG. 32,[35][36][37][38][39][40][41][42][43][44][45][46] In fact, the production of LIG by such scribing process has now been accomplished using other carbon sources besides the polyimide, as for instance cloth, paper or even food, 41,43,47 as well as other laser wavelengths. 48 Moreover, its application extend from microuidic devices, sensors, optoelectronic devices, microsupercapacitors, to catalysts, among others.…”
Section: Introductionmentioning
confidence: 99%